Pelatihan Belajar Bahasa Inggris Dasar Pada Siswa SDN Bicorong II Pamekasan - Dandy Firatama, Aditya; Rizqi Azam Syaichon; Wa’idul Hasan; Fakhrur Rozi Arifin; Al Farisi; Nurul Ilmi (STMIK Royal, 2025)
Abstract: English is a universal language used in many countries around the world. SDN Bicorong II is located in Bicorong Village, Pamekasan Regency. Students often struggle with English and are reluctant to learn it. As a means to improve their English communication skills, a tutoring program offers basic English instruction to SDN Bicorong II students. A total of 29 students participated in the community service program for basic English tutoring. Each session lasted 90 minutes and was conducted over two days. Socialization, instruction, mentoring, and assessment were part of the approach implemented to provide basic English tutoring to students. Only 17.24% of students who completed the test passed, while 82.76% of the other students failed, based on the learning outcomes of elementary school students before the tutoring program. The overall average score was 62. The results after the basic English tutoring program showed that of the 29 elementary school students who took the test, 86.21% passed and 13.79% failed. The data shows that students who did not pass the test got a score range of 55-69 while students who passed the test got a score range of 70-100. The average score of 29 students was 76. Thus, basic English tutoring can improve the abilities and learning outcomes of students at SDN Bicorong II. Keywords: basic english; communicative approach; evaluation; learning; training Abstrak: Bahasa Inggris merupakan bahasa universal yang digunakan di banyak negara di seluruh dunia. SDN Bicorong II terletak di Desa Bicorong Kabupaten Pamekasan. Para siswa biasanya kesulitan berbahasa Inggris dan enggan mempelajarinya. Sebagai sarana untuk meningkatkan kemampuan komunikasi bahasa Inggris mereka, program bimbingan belajar menawarkan pengajaran bahasa Inggris dasar kepada siswa SDN Bicorong II. Sebanyak 29 siswa berpartisipasi dalam program pengabdian masyarakat bimbingan belajar bahasa Inggris dasar. Setiap sesi berdurasi 90 menit selama dua hari. Sosialisasi, instruksi, pendampingan, dan penilaian merupakan bagian dari pendekatan yang diterapkan untuk memberikan bimbingan belajar bahasa Inggris dasar kepada siswa. Hanya 17,24% siswa yang menyelesaikan tes lulus, sementara 82,76% siswa lainnya tidak lulus, berdasarkan hasil belajar siswa sekolah dasar sebelum program bimbingan belajar. Skor rata-rata keseluruhan adalah 62. Hasil setelah dilakukan bimbingan belajar bahasa Inggris dasar menunjukan bahwa dari 29 siswa SD yang ikut tes 86,21% siswa lulus tes dan 13,79% siswa tidak lulus. Data menunjukan bahwa siswa tidak lulus tes mendapat rentang nilai 55-69 sedangkan siswa yang lulus tes mendapat rentang nilai 70-100. Hasil nilai rata-rata dari 29 siswa adalah 76. Dengan demikian bimbingan belajar bahasa Inggris dasar dapat meningkatkan kemampuan dan hasil belajar siswa SDN Bicorong II. Kata kunci: bahasa inggris dasar; evaluasi; pelatihan; pembelajaran, pendekatan komunikatif